Clinical case of tuberculous meningoencephalitis in a child - Seriakova, Iryna; Palatna, Liudmyla (The Ukrainian Scientific Medical Youth Journal, 2025)
Tuberculous meningoencephalitis remains an urgent medical and social problem due to high mortality, difficulty in diagnosis, and an increase in the number of cases among children. Aim of the study was to increase awareness and alertness of medical workers regarding the possibility of tuberculous meningoencephalitis in children based on the demonstration of a clinical case. Materials and methods. We conducted an empirical, descriptive study of a clinical case of tuberculous meningoencephalitis in a 1.5-year-old child during inpatient treatment at the Kyiv City Children’s Clinical Infectious Diseases Hospital. The study was performed in accordance with the principles of the Declaration of Helsinki. The study protocol was approved by the hospital’s bioethical committee (protocol №3 dated 24.09.2025). Results and their discussion: A 1.5-year-old child was admitted to the hospital on the 7th day of illness with complaints of fever up to 38.5°C, lethargy, and nausea. When examining the child, the BCG scar was absent. On the 3rd day of inpatient treatment, the condition showed negative dynamics. Fever, severe lethargy, repeated vomiting were observed. The child does not walk, does not sit, and the hands in the left limbs are limited. Left-sided pneumonia was detected on the X-ray. The child’s condition deteriorated in dynamics. According to the examination, laboratory and instrumental examinations, meningoencephalitis, cerebral edema, coma, convulsive syndrome, left-sided hemiparesis, bilateral lung damage were diagnosed. MRI revealed signs of encephalitis in the basal nuclei, the knee of the corpus callosum and the medial parts of the right temporal lobe. Mycobacterium tuberculosis (G+R-) was isolated from the cerebrospinal fluid by PCR, and a diagnosis of nervous system tuberculosis and meningoencephalitis was established. The objective condition upon admission to the intensive care unit is extremely severe due to neurological symptoms on the background of specific CNS damage, manifestations of cerebral edema, intoxication syndrome. The child’s general condition rapidly deteriorated. Intestinal paresis, anuria without response to diuretics, anemia and thrombocytopenia, decompensated metabolic acidosis - corrected, DIC syndrome. Consciousness - coma of the III degree. On the FOUR scale = 0b. Diffuse muscular hypotension, areflexia. Pupils are dilated D = S, no photoreaction. Body temperature 35, 60 C. Severe peripheral edema. Blood pressure 71/30 mm Hg. Heart rate 94 beats / min. Heart sounds are muffled. Despite the treatment, the case ended fatally. Conclusions. Vigilance regarding the possibility of tuberculous meningoencephalitis in children is important in the diagnosis of infectious diseases.